(untitled) (Filološke pripombe, 2019)
The article deals with the specifities of the USA`s perception by Russian philosophers in the 1840th years of the XIX century. The author compares the views of N. Turgenev, A. Herzen, I. Kireevsky, K. Aksakov on the matter. There is shown, that the interest to history, culture and social structure of the USA is logically included in the context of the Russian philosophers` speculations on the Russian historical way – both the Westerners and the Slavophiles. The author reveals differences and resemblances in their ideas and opinions on the American model of social progress. Also special attention is focused on the peculiarities of the development of Russian philosophers` positions, concerning the “American theme”. At the same time the author concentrates on the evolution of the N. Turgenev`s, Herzen`s views on America, paying attention to their philosophical and social positions on the whole.